Childhood Cancer Survival, 2006-2012 Cohorts of Mexican Institute of Social Security Beneficiaries at the Central-South Region of Mexico - Castro-Ríos, Angélica; Martínez-Valverde, Silvia (Frontiers in Oncology, 2022)
This study of childhood cancer survival is the first based on incident cases for IMSS´s affiliated in Mexico. It corresponds to the central region, from two medical networks: “La Raza” and the “SXXI” network, which represents 27% of all children.It is an observational cohort study from 2006 to 2012 to estimate 5-year observed survival of the minor of 18 years old, identified in the Central-South Region Registry of Children with Cancer. Survival of cases was carried out through the active and passive search. Survival rates were adjusted by Kaplan-Meier´s method, the analysis of equality of survival functions was evaluated for some clinical and socioeconomic variables. Results. The study included 2,357 minors; the 5-year observed survival was 56.1% with a median of 3.4 years. The 5-year survival in cases with a diagnosis of leukemia was 53.5%, while for solid tumors 57.9%. The median time of death was 1 year. The types of cancer with a survival greater than 70% were group V-retinoblastoma (87.2%), IIa-Hodgkin's lymphoma (86.8%), Xc- gonadal tumors (83.3%), IId-miscellaneous lymphomas (80%), IVa-nephroblastoma (79.5%) and IIc-Burkitt's lymphoma (75.4%). While the lowest survival rates were observed in group VIII-bone tumors (32.3%), III-CNS (44.1%), and IX-soft tissues (46.8%). Differences were found in some variables, which could help to identify areas of improvement, in relation to access and clinical management. Conclusions. Survival results in the 2006-2012 cohorts show a significant gap in relation to the maximum level achievable, and still below the goal proposed by the WHO for 2030.